STRUCTURAL-PARAMETRIC SYNTHESIS OF THE AUTOMATIC CONTROL SYSTEM FOR A OIL ROAD HEATER - VASYLENCHUK, MYKHAILO; HORBIICHUK, MYKHAILO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Unlike direct oil heaters, where the pipe carrying the oil comes into direct contact with the flame, in line heaters, the oil is heated indirectly through a water bath. The bath contains a bundle of tubes through which the oil flows, as well as a fire tube. In the combustion chamber, natural gas is burned, and as it moves through the fire tube, it transfers heat to the intermediate heat carrier (water). The heat flow from the water then heats the oil flowing through the tube bundle.This indirect heat transfer process promotes uniform heating and reduces the likelihood of hot spots. Hot spots often occur in heaters with direct heating by flue gases, leading to the accumulation of deposits on the working fluid side. The presence of such spots can result in equipment degradation and the occurrence of accidents.On the other hand, the presence of a large-volume water bath causes significant inertia in the "fuel gas flow–oil outlet temperature" control channel, which requires new circuit design solutions to improve control process quality indicators.The synthesized structural diagram of the automatic control system for the oil heating process in the line heater includes PI and PD controllers. The PI controller is placed in the direct control loop, while the PD controller is included in the negative feedback loop that encompasses the control object.To calculate the tuning parameters of the PI/PD controllers, a combined method was used, consisting of two stages.In the first stage, the parameters for tuning the PI/PD controllers are determined using the s-plane method, where the parameters are functions of the real part of one of the roots of the characteristic equation.In the second stage, a generalized quadratic quality criterion of the control process is minimized, which is a function of a single variable—the real part of one of the roots of the characteristic equation. It was established that the synthesized structural diagram of the automatic control system for the oil heating process in the line heater reduced the regulation time by 68.9% without overshoot, compared to a cascade-linked automatic control system.
Keywords: oil heater; control system; structure; parameters; PI/PD controllers; settings